(3QSGdI aj CUhd GdMSGHs - (3Ydj Hf CMeO GdSgdjs
(3ChdgG (B:s
(3GYde Cf CUhd GdMSGH cdgG KdKI , GdVQH hGdbSeI hGdfSHI hgj JHfi Ydi eYQaI KdGKI CTjGA hgj GdeQGJH hGdYbhO hGdGSeGA s
(3BNQgG (B:s
(3HGH eYQaI cShQ GdGda GYde Gf GdGda fUaGf fUagG NeS eGFI KdKGf hNeSGf NeSI YTQ CUd aGYde Pdc s
(3GdfSNI HgG MhGTs
(3YdjgG bQGAIs
(3eUOQ GbJfGA GdCUd (B:s
(3eLdS ThQGi (B(3/7189) s
Keywords: (3GdQjGVjGJs